Philosophy of Science and Religion - Ramachandran, G N (Journal of Dharma, 1983)
In this paper, I shall attempt to present a brief picture of what science is, and how scientists view the great problems irnposed by religious concepts on the minds of everybody—problems such as "What is the nature of things?" "What force drives the Universe" and "What causes order to exist in Nature?" , and perhaps touch upon questions like— ’ ’Is what we see, and hear, and feel, the real nature of things, or is it only a view of these as seen by man?" In trying to understand such aspects of knowledge, science and philosophy mingle with one another. In fact, the answers to many of these questions were given more than 2,000 years ago by philosophical thinkers of India, Greece and other Countries, although science has advanced to its full maturity only within the last century or so.